Response of Maize to Humic Acid and Foliar Salicylic Acid Application - Shamsur Rehman; Maleeha Mehboob; Samiullah Kakar; Saad Muhammad; Abdul Salam Khan; Mian Zawar Ulhaq; Zaryab Shah; Marzia Alam; Kareem Ashfaq; Sher Azam (International Journal of Sustainability in Research, 2023)
Humic acid to soil has positive effects on soil properties that result in improved soil fertility and maize yield. Maize growth and yield can also be enhanced by foliar application of salicylic acid. A field experiment was carried out at Agronomy Research Farm, The University of Agriculture Peshawar during summer season, 2021 to evaluate the response of maize to humic acid and foliar salicylic acid application. Results revealed that plots treated with humic acid at the rate of 15 kg ha-1 significantly increased plant height (217.8 cm), grains ear-1 (507), thousand grains weight (302.3 g) and grain yield (5309 kg ha-1). Salicylic acid with 750 mg L-1 showed taller plants (221.1 cm), maximum grains ear-1(502), heavier thousand grains weight (299.1 g) and maximum grain yield (5171 kg ha-1) which is statistically similar with the application of salicylic acid foliar spray at the rate of 500 mg L-1. Interaction between humic acid and salicylic acid was found to be non-significant except in case of grains ear-1 and grain yield. It was concluded that humic acid at the rate of 15 kg ha-1 and salicylic acid foliar spray of 750 mg L-1 is recommended for higher grain yield of maize in Peshawar.